2020
DOI: 10.2298/sos2003245d
|View full text |Cite
|
Sign up to set email alerts
|

Sinterability and characterization of Ag/Al2O3 metal and ceramic matrix composites processed by mechanical milling

Abstract: In this research, the sinterability of Ag/Al2O3 milled powders with 10 and 90 wt%Ag were investigated. The powders were consolidated by two different processes including conventional and spark plasma sintering. The conventionally sintered composites with 90 wt%Ag were further densified by cold pressing and subsequent annealing at 700?C. The microstructural evaluations confirmed a fine dispersion of the constituents within the microstructure of the spark plasma sintered composites. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In this study, on the other hand, in parallel with the study done by Rao and his colleagues, it was found that an increase in hardness value occurred with the increase of the reinforcement material. In a study conducted by Davodi and colleagues [17], Ag/Al 2 O 3 metal matrix composites were fabricated by mechanical milling. They showed that the hardness value (HV) increased with the Al 2 O 3 content.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, on the other hand, in parallel with the study done by Rao and his colleagues, it was found that an increase in hardness value occurred with the increase of the reinforcement material. In a study conducted by Davodi and colleagues [17], Ag/Al 2 O 3 metal matrix composites were fabricated by mechanical milling. They showed that the hardness value (HV) increased with the Al 2 O 3 content.…”
Section: Resultsmentioning
confidence: 99%
“…The crack process in Ca-PWA crystals had followed the appearance of smaller crystals with the average size of several micrometers (~ 2 μm). Concerning Ca-PWB sample, SEM image have shown increased micrometer size (~ 20 μm) due to agglomeration of crystals [33][34][35][36].…”
Section: Tab IImentioning
confidence: 99%
“…Different methods have been developed to apply biocompatible coatings including plasma spray [3][4][5], mechanical milling [6], pulse laser [7][8][9], aerosol [10,11], sol-gel [12,13], electro-deposition [14], pulse electron [15,16], EPD method [17]. These methods can be employed as processing techniques for the fabrication of coatings and small parts with complicated shapes [17].…”
Section: Introductionmentioning
confidence: 99%